2023
DOI: 10.34133/research.0090
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Thermally Activated Delayed Fluorescence Materials for Efficient Scintillation

Abstract: Organic scintillators, materials with the ability to exhibit luminescence when exposed to X-rays, have aroused increasing interest in recent years. However, the enhancement of radioluminescence and improving X-ray absorption of organic scintillators lie in the inherent dilemma, due to the waste of triplet excitons and weak X-ray absorption during scintillation. Here, we employ halogenated thermally activated delayed fluorescence materials to improve the triplet exciton utilization and X-ray absorption simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The RL intensity of organic fluorescent scintillators is positively correlated with factors of X-ray attenuation coefficient (μ∝Z 4 ), the fluorescence quantum yield (Ф f ) and the carrier trans-port efficiency (𝜂). [14,20,21] By comparing the X-ray absorption abilities of BPA and BPA-X while ignoring resonant absorption edges, [3] we observed that the X-ray absorbance follows the order of BPA-I (Z max = 53, K 𝛼 = 33.2 keV) > BPA-Br (Z max = 35, K 𝛼 = 13.5 keV) > BPA-Cl (Z max = 17, K 𝛼 = 2.84 keV) > BPA (Z max = 6, K 𝛼 = 0.278 keV), as can be seen in Figure 2a. Besides, the X-ray attenuation efficiencies also improved significantly (Figure S11, Supporting Information) and it indicates that the introduction of halogen atoms significantly enhances the Xray absorption ability of the materials, thereby leading to an improvement in the RL intensity of the materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RL intensity of organic fluorescent scintillators is positively correlated with factors of X-ray attenuation coefficient (μ∝Z 4 ), the fluorescence quantum yield (Ф f ) and the carrier trans-port efficiency (𝜂). [14,20,21] By comparing the X-ray absorption abilities of BPA and BPA-X while ignoring resonant absorption edges, [3] we observed that the X-ray absorbance follows the order of BPA-I (Z max = 53, K 𝛼 = 33.2 keV) > BPA-Br (Z max = 35, K 𝛼 = 13.5 keV) > BPA-Cl (Z max = 17, K 𝛼 = 2.84 keV) > BPA (Z max = 6, K 𝛼 = 0.278 keV), as can be seen in Figure 2a. Besides, the X-ray attenuation efficiencies also improved significantly (Figure S11, Supporting Information) and it indicates that the introduction of halogen atoms significantly enhances the Xray absorption ability of the materials, thereby leading to an improvement in the RL intensity of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Scintillators possess the ability to emit ultraviolet or visible light upon X-ray irradiation, which has garnered considerable attention in recent years due to their crucial applications in areas excitons through the heavy atom effect. Subsequently, Ma et al [13] and Wang et al [14] utilized halogen atom substitution in 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene and 10-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl-9,9-dimethyl-9,10dihydroacridine thermal activated delayed fluorescence materials (TADF), respectively. Both bromine-substituted TADF molecules exhibited the highest RL intensity among the tested compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, halide perovskites suffer from severe self-absorption due to their inherent bandgap emission, limiting their scintillation performance . Moreover, their ionic structure makes them highly susceptible to moisture-induced instability. , On the other hand, scintillators based on organic luminescent molecules or metal clusters show reduced self-absorption but lack sufficient X-ray stopping ability. , Therefore, the quest for stable scintillator materials that simultaneously address self-absorption issues and offer strong X-ray stopping power remains crucial for advancing the scintillation performance.…”
mentioning
confidence: 99%
“…25,26 On the other hand, scintillators based on organic luminescent molecules or metal clusters show reduced self-absorption but lack sufficient X-ray stopping ability. 27,28 Therefore, the quest for stable scintillator materials that simultaneously address self-absorption issues and offer strong X-ray stopping power remains crucial for advancing the scintillation performance.…”
mentioning
confidence: 99%